The Effect of Bring Your Own Device (BYOD) Adoption on Work Performance and Motivation - Doargajudhur, M.; Dell, Peter (IACIS, 2018)
Many organizations are considering Bring Your Own Device (BYOD) programs, in which employees are permitted to use personal mobile devices for work-related purposes. Based on the job demands–resources model, this study empirically investigated the effects of BYOD adoption on employees’ motivation and perceived job performance. Using a sample of 400 full-time employees from different occupational sectors in Mauritius, this study adopted structural equation modeling to test the hypotheses using AMOS version 22. Results show that BYOD has a significant positive relationship with technology self-efficacy (TSE), perceived workload and perceived job autonomy, while perceived job autonomy is a positive antecedent to perceived workload. In addition, TSE, perceived job autonomy and perceived workload, in turn, influence perceived job performance, while perceived job autonomy and perceived job performance were found to be significant determinants of work motivation. Implications of these findings, limitations and potential research avenues are also discussed.